2017
DOI: 10.5209/soci.55830
|View full text |Cite
|
Sign up to set email alerts
|

¿Cómo influye el sistema de protección en el bienestar subjetivo de los adolescentes que acoge?

Abstract: Resumen. El bienestar subjetivo es un componente esencial de la calidad de vida. Conocemos muy poco sobre el bienestar subjetivo de los niños y niñas, y menos aún de los adolescentes de colectivos vulnerables como los que están acogidos por el sistema de protección. El objetivo de este trabajo es estudiar cómo influye el sistema de protección en el bienestar subjetivo de los adolescentes que acoge a partir de sus propias percepciones, evaluaciones y satisfacciones. Se trata de un estudio transversal realizado … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
(18 reference statements)
0
6
0
9
Order By: Relevance
“…That desire may express the devotion and need to be linked with their families and an ambiguous loss that attachment theory can explain (Bolbwy 1951), or maybe residential centres do not provide a consistent alternative in this matter, because caregivers' changes and shifts rotation may originate a sense of uprooting. Llosada-Gistau et al (2017) highlighted the importance for adolescents at risk of the relationship with educators, a key factor of resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That desire may express the devotion and need to be linked with their families and an ambiguous loss that attachment theory can explain (Bolbwy 1951), or maybe residential centres do not provide a consistent alternative in this matter, because caregivers' changes and shifts rotation may originate a sense of uprooting. Llosada-Gistau et al (2017) highlighted the importance for adolescents at risk of the relationship with educators, a key factor of resilience.…”
Section: Discussionmentioning
confidence: 99%
“…In Catalonia (Spain), Llosada-Gistau et al (2017) demonstrated how adolescents living in residential care reported lower SWB in all life domains when compared to those in foster care (kinship and non-kinship). Variables that might have an influence on their subjective well-being, include their interpersonal relationships, particularly with friends, and the possibility of being involved in decision-making processes.…”
Section: Introductionmentioning
confidence: 99%
“…Exploratory analyses were performed before the mediation models (i.e., descriptive, mean differences and correlation analysis) considering that previous evidence revealed a set of differences on children's rights, well-being and bonding to the place according to gender, age and time in residential care (Dinisman et al, 2012;Llosada-Gistau et al, 2017a;Llosada-Gistau et al, 2017b; Uyan-Semerci, Erdogan, Akkan, Muderrisoglu & Karatay, 2017). Based on our results from these exploratory analyses, these sociodemographic variables were controlled for in the mediation analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Not only do these young people show more complex risk factors and difficulties (e.g., special education needs), compared to foster children (Llosada-Gistau et al, 2017b), but also their psychological functioning seems to be poorest. Worse subjective well-being is reported by young people in residential care, compared with children in other out-of-home placements (Llosada-Gistau, Montserrat & Casas, 2017a;Llosada-Gistau et al, 2017b). Also, young people in residential care report lower levels of subjective and psychological wellbeing compared with their peers in the family (Crous, 2017;Dinisman, et al, 2012;Llosada-Gistau, Montserrat & Casas, 2015).…”
Section: Blinded Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation